2022
DOI: 10.1007/s40940-022-00175-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of composition on the durability and weathering of flat glass

Abstract: Among the environmental factors affecting glass weathering are humidity, exposure time, temperature, and the presence of pollutants in the atmosphere. Notwithstanding that the weathering produced depends on numerous factors, the important weathering effect of high humidity may be specifically mitigated by using a good chemical composition for the glass. To evaluate this relationship, flat glass samples from three suppliers were studied. The chemical composition of the samples was determined and the variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Lead-barium glass developed from Chinese Chu culture has added lead ore as a flux in the firing process, and the content of lead oxide (PbO) and barium oxide (BaO) is relatively high [8,13]. Potassium glass is made of high potassium content substances such as plant ash as a flux, which is mainly popular in the south of China, Lingnan, Southeast Asia, India and other regions [2,4,11]. Glass can be divided into high-potassium glass and lead-barium glass [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…Lead-barium glass developed from Chinese Chu culture has added lead ore as a flux in the firing process, and the content of lead oxide (PbO) and barium oxide (BaO) is relatively high [8,13]. Potassium glass is made of high potassium content substances such as plant ash as a flux, which is mainly popular in the south of China, Lingnan, Southeast Asia, India and other regions [2,4,11]. Glass can be divided into high-potassium glass and lead-barium glass [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of sodium in the system conspicuously affects the coefficient of thermal expansion by depolymerizing the network. 18,21,22 29 shows the coefficient of thermal expansion (in blue) increases as a function of the increase in sodium oxide concentration. This result is expected and represents the network being globally depolymerized by sodium ions.…”
Section: Naps Glass Systemmentioning
confidence: 99%
“…38,[129][130][131] Some studies also indicate that chemical durability is affected not only by the chemical composition but also by the proportion of linkages that are susceptible to hydrolysis. 22,131,132 For instance, wellestablished studies showed that the addition of alumina to phosphate glasses can strengthen their chemical durability due to the formation of Al-O-P linkages. [33][34][35][36] Additionally, the weathering of a glass is commonly initiated by the interaction of network modifiers, such as Na + ion, with neutral water from the atmosphere.…”
Section: Span Glassesmentioning
confidence: 99%
See 2 more Smart Citations